1988
DOI: 10.1002/art.1780310404
|View full text |Cite
|
Sign up to set email alerts
|

Augmented interleukin‐1 production and hla–dr expression in the synovium of rheumatoid arthritis patients

Abstract: Potent interleukin‐1 (IL‐1) activity was detected in culture supernatants from synovium, obtained by arthroscopy, from rheumatoid arthritis (RA) patients but not from non‐RA patients. Production of IL‐1 by RA synovium correlated well with findings of inflammation on arthroscopy and HLA–DR expression in immunohistochemical staining. Furthermore, there was a positive correlation between IL‐1 production from RA synovium and joint changes detected on roentgenograms. These findings strongly suggest that IL‐1 might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 205 publications
(70 citation statements)
references
References 27 publications
5
65
0
Order By: Relevance
“…These data indicated that CIA mice display marked upregulation of IL-1b in joints accompanied by synovial growth similar to human RA. 1,2,4 Intramuscular gene therapy using IL-1Ra DNA inhibits CIA in mice As a plasmid expression vector for intramuscular gene therapy, we used pCK, which has been shown to drive a high level of gene expression in the skeletal and cardiac muscles of mice. 22,23 The human IL-1Ra coding sequence was cloned to pCK, resulting in pCK-IL-1Ra (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated that CIA mice display marked upregulation of IL-1b in joints accompanied by synovial growth similar to human RA. 1,2,4 Intramuscular gene therapy using IL-1Ra DNA inhibits CIA in mice As a plasmid expression vector for intramuscular gene therapy, we used pCK, which has been shown to drive a high level of gene expression in the skeletal and cardiac muscles of mice. 22,23 The human IL-1Ra coding sequence was cloned to pCK, resulting in pCK-IL-1Ra (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…1 Although the causes of RA are not fully understood, various experimental and clinical studies suggest that proinflammatory cytokines, particularly interleukin-1 (IL-1) among others, have an important role in RA pathogenesis. [2][3][4][5] The IL-1 receptor antagonist (IL-1Ra) is a natural protein that competitively inhibits the binding of IL-1b and IL-1a to IL-1 receptor types I and II in humans and various animals, and improves the inflammatory symptoms of arthritis in experimental animal models. 1,[6][7][8][9][10] Several independent clinical trials have been completed in which the recombinant IL-1Ra protein has been administered for a long-term period to patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…Synovial cells from an RA patient were obtained during total knee replacement, as described elsewhere (9). Binding experiments were performed as previously described (10).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, preliminary experiments reveal the presence of IL-1 and IL-6 activities in culture supernatants of synovial tissues and SF cells from patients with this arthropathy; which cells are responsible for the production of these cytokines is still unknown. We have already reported that IL-1 and IL-6 productions are augmented by the proliferating synovial tissue in RA and other inflammatory arthropathies (13,14). These findings suggest that cytokines, including IL-1, IL-6, and other factors, might be produced by the HTLV-I-infected cells themselves or as a result of the immune reaction to HTLV-I infection in the synovium.…”
Section: Discussionmentioning
confidence: 80%
“…Immunohistochemical staining was performed using a modification of the method described previously (13,14). Briefly, frozen sections or smears were air-dried and fixed with cold acetone for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%